Effect of Tire Pressure Factor Toward Fuel Consumption of Passenger Vehicle - Premdip Singh Koldip Singh; Muhamad Asri Azizul; Syabillah Sulaiman (Journal of Automotive Powertrain and Transportation Technology, 2025)
Total amount of car on street is increasing and it concern the scientist, politician and the public regarding the air pollution is caused. Air pollution due to motorized vehicle can be harmful to the environment and humans. The main objective of the project is to find out how the tire pressure effects the fuel consumption of passenger car. Perodua Myvi was used in this experiment to measure the fuel consumption at various tire pressure which are 170, 210, 250 kPa. This experiment conducted in UTHM Pagoh where the road stretch to 4.7 km but the desired distance is 51.7 km so, the driver has to drive 11 times around UTHM Pagoh road. This experiment conducted at least three times at different tire pressure and after each test drive the fuel consumption was recorded using On-Board Diagnostic II (OBD II) under dry weather.